Rancang Bangun Alat Penyiraman, Pemupukan, Dan Penyemprotan Pestisida Pada Bibit Kelapa Sawit Berbasis Internet of Things - Wawan Hermanto; Wahyuni Eka Sari; Abdullah Hanif (Riau Jurnal Teknik Informatika, 2026)
Manual care for oil palm seedlings during the nursery stage is often inefficient, labor-intensive, and prone to inaccuracies regarding the dosage and frequency of water, fertilizer, and pesticide application. This study aimed to design and develop an integrated Internet of Things (IoT)-based automation system that combines watering, liquid fertilization, and pesticide spraying functions into a single device capable of remote monitoring and control. The system was constructed using an ESP32 microcontroller, a soil moisture sensor (YL-69), a rain sensor (FC-37), a DS3231 RTC module, three DC pumps, and relays; sensor data is transmitted to the Firebase Realtime Database and displayed via a web dashboard. Test results demonstrated that the soil moisture sensor automatically activates the pump when levels fall below a 30% threshold, the rain sensor responds to weather changes in under one second, and data communication remains stable with an average delay of 1–2 seconds. This IoT system contributes to improved seedling care efficiency, evidenced by an average seedling height growth of 15 cm over 30 days, compared to 12 cm using manual methods.